Prediction of foamability of polyethylene terephthalate using viscous and elastic parameters. Issue 6 (30th October 2017) - Yang, Zhaoping; Xin, Chunling; Mughal, Waqas; Wang, Zeming; Bai, Xue; He, Yadong
Abstract: Rheological behavior and foamability of polyethylene terephthalate (PET) with different molecular structures were investigated. The aim of this study was to find out the viscous and elastic parameters which can predict the foaming properties of PET. It is found that the foams of strain hardening PET have high expansion ratios and fine cell morphologies. This is correlated with the contribution of strain hardening to the improvement of melt strength and failure strain during elongational experiments. Basing on the fact that foamability of a material is governed by its strain hardening (a pure elastic behavior), a viscous parameter (complex viscosity), and an elastic parameter (loss tangent) obtained from dynamic shear rheology are well linked to the expansion ratios of foams. These two parameters formed an optimized viscoelastic window, which is suitable for foaming. This means the foamability of PET can be determined by viscous and elastic parameters without consideration of molecular constitution.